Internet connectivity disruption in Burundi (Burundi) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Burundi. Data sourced from IODA.
Network Disruption Incident ID: BI-2026-0004. Severity: critical. Confidence: 65%